2016
DOI: 10.5551/jat.33514
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Accumulation Product and Hypertension Related to Stroke: a 9.2-Year Prospective Study Among Mongolians in China

Abstract: Cox proportional hazards models and receiver operating characteristic (ROC) curves were used to evaluate the associations between LAP, hypertension, and stroke incidence. Results: During the follow-up period, a total of 121 stroke events were observed. Participants with higher LAP were associated with higher risk of stroke [adjusted hazard ratio (HR), 1.67; 95% confidence interval (CI), 1.08 -2.58] than the participants in the lower LAP group. However, no significant dose -response relationship was detected be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
4
17
0
2
Order By: Relevance
“…It is confirmed by research regarding other ethnic groups [5,25,26]. Some papers report a positive relation between HT occurrence and the value of LAP [11,27]. In our study, hypertensive patients also had a significantly higher LAP compared to people without hypertension.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is confirmed by research regarding other ethnic groups [5,25,26]. Some papers report a positive relation between HT occurrence and the value of LAP [11,27]. In our study, hypertensive patients also had a significantly higher LAP compared to people without hypertension.…”
Section: Discussionsupporting
confidence: 88%
“…This confirmed the results obtained on a bigger population by Wakabayashi [28], who studied over 36 000 middle-aged men. Zhong et al [27] suggest that reducing LAP has an anti-hypertensive effect on people with arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…LAP, a new obesity index computed from WC and triglyceride (TG), is a useful indicator of visceral fat,12 as demonstrated by Kahn in 2005 13. Some studies suggest that LAP can also be used to identify metabolic syndromes,14 15 type 2 diabetes mellitus,16 stroke17 and arterial stiffness 18. Additionally, several cross-sectional studies conducted in Japan,19 India14 and Brazil indicate that LAP significantly associated with cardiovascular disease and is a better indicator than BMI for identifying cardiovascular risk 13 20.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid accumulation product (LAP), which is calculated as a combination of waist circumference (WC) and fasting plasma triglyceride (TG) levels, has been proposed as an alternative measure of excessive lipid accumulation [ 12 ]. Recently, a growing number of studies have shown that LAP is a powerful marker for diabetes [ 13 ], metabolic syndrome [ 14 , 15 ], and insulin resistance [ 16 ] in the general population and associated with risk of cardiovascular diseases [ 17 19 ]. Given the close associations between diabetes, metabolic syndrome, insulin resistance, and hepatic steatosis [ 20 ], these findings inspired us to explore whether LAP could also be a powerful index for identifying NAFLD.…”
Section: Introductionmentioning
confidence: 99%